CONSUMER PROTECTION IN INTERNET SALES – DEGREE OF HARMONIZATION WITH THE EUROPEAN UNION LAW - Ranđelović, Dragana; Ljajić, Samir (The European Journal of Applied Economics, 2017)
The topic of this paperwork is the harmonization of contract law, as a process which represents, on one hand, the basic assumption for the creation of a unique market in the European Union, and on the other, a necessary condition for Serbian membership in it. Firstly, the authors will tend to answer some general questions regarding the concept, significance and challenges of the harmonization of contract law. In Serbia, in the field of contract law, primarily Internet sales, the process or harmonization is going in good direction. A series of laws and other bylaw regulationsregarding requirements and standards of the European Union has been introduced. However, since this field includes a matter which hasn’t been regulated so far, laws have a lot of shortcomings which cause problems during their application. One of the set priority requirementsis the question of consumer protection. An array of regulations has been introduced in the European Union guaranteeing consumer protection, their right to information, education, health protection, safety, economic and legal interest safety, thereby reaching the highest degree of law development and legal consumer protection. Therefore, it is necessary to conduct a rapid and efficient harmonization with the regulations of the European Union. The authors will tend to determine to which degree the regulations in this field are harmonized with the requirements and standards of the European Union, provide answers to some basic questions and issues that appear in practice, as well as to point out to the need of harmonization in this field. Given the actuality and mass state of Internet sales, questions and issues of consumer protection will be set within its boundaries. Key words: Consumer protection, harmonization of contract law, Internet sales, e-commerce